A study of cleanliness level at cafeteria / Nurazlina Mohamad Zaib - Mohamad Zaib, Nurazlina (Faculty Architecture, Planninng and Surveying, 2014)
This thesis is about cleanliness level at cafeteria Faculty Architecture, Planning and Surveying, (FSPU) Universiti Teknologi MARA (UiTM) campus Shah Alam. Respondents from the user cafeteria are the key to succeed this study where the questionnaire are distributed to the staff UiTM, staff cafeteria, students and other user. In addition, there are have an interview session between the food operator at the cafeteria and the person who are in charge in this studies.the issues that are arise at FSPU cafeteria are the cafeteria deteriorated to such an extent seized by the authorities. There are many possibilities that arise from hygiene problems in the cafeteria. One of the causes is food and beverage waste. The main objective of the study are to identify the level of cleanliness which included To identify and evaluate cleanliness level at cafeteria, To investigate the problem encountered by cafeteria that prompted it to be sealed by the uitm management, To recommend the effective way to keep the cafeteria clean and always be in satisfactory level. The analysis was done based on the percentage and min. The finding of this study showed that satisfaction from uitm shah alam FSPU's cafeteria user about the level of hygiene at cafeteria and ultimately discover the reasons and strategies to solve concerning the quality of cleanliness.